Perancangan Exhibition Booth Untuk Wedding Photography Dengan Material Cardboard - Natashia Angelica Reynalda Harijono (Intra, 2017)
To participate in an exhibition, booth that attracts attention is required. Without exception, for wedding photographers who participated in a wedding exhibition. The problem is, building materials, furnitures, and construction service, requires big amount of cost. These costs can be saved if the materials can be used repeatedly and the construction can be done independently.During this time, materials used in booth constructions were using processed wood products, that are rigid and heavy. As another alternative, cardboard can be utilized more by processing the material into an exhibition booth.The design method stages are to analyze the needs of users and booth design, before the design stage begins. The design concept adopted is Showing Off Life Simply And Naturally, which is manifested in the form of 3 themed booth designs which are Curve, penstARgon, and Home. Booth as a whole measuring 5x3 meters, each of them divided into 2x3 and 3x3 meters sized booth. The construction system used is knock-down system so that the booth can be distribute easily and reuseable.